Implementasi Nilai-Nilai Moderasi Beragama Dalam Pembelajaran PAI - Evita Yuliatul Wahidah; Susi Susi (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
This study examines the implementation of religious moderation values in Islamic Religious Education (PAI) at SMKN 1 Garut, Indonesia, to support inclusive education amid religious and ethnic diversity. SMKN 1 Garut has approximately 25–30 non-Muslim students from Christian, Catholic, and Sunda Wiwitan faiths, which requires attitudes of tolerance, justice, and balance in social interactions. Religious moderation aims to instill these attitudes in accordance with the teachings of the Qur’an and Pancasila values. This study describes the implementation of religious moderation values, the strategies employed, and the challenges encountered. A qualitative descriptive method was used, with data collected through observation, interviews, and documentation. Data were analyzed through reduction, presentation, and conclusion drawing, with validity ensured through triangulation. The results show that religious moderation has been integrated into the curriculum, social interactions, and school culture. Teachers act as facilitators in instilling values of tolerance, balance, and justice. Strategies include inclusive approaches, varied learning models, and programs such as Morning Share and Smarttren that promote moderate attitudes. The challenges faced include a lack of religious teachers for non-Muslim students, limited teaching methods, and teachers’ low proficiency in technology.Keywords: Implementation of Religious Moderation Values, Islamic Religious Education Learning